Corrosion Occurring in the Technological Processes of Oil and Gas Processing and Methods of its Prevention (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article develops and provides information about the main types of corrosion, the causes of their occurrence, methods and means of prevention and elimination in the process of oil and gas pre-processing.